Modular Synthesis of New Bicyclic Carbene Precursors - Li, Jie; Yao, Jiaqi; He, Weiping; Yang, Fan; Liu, Xiaoming (Letters in Organic Chemistry, 2019)
A series of new N-heterocyclic carbene (NHC) precursors, containing bicyclic pyrrolo[1,2- c]imidazole framework, were prepared from N-(tert-butoxycarbonyl)-L-proline (1-Boc-L-proline). The sequential attachment of nitrogen nucleophiles and subsequent ring closure gave the desired bicyclic NHC precursors in good yields. The structures of these new NHC precursors were determined on the basis of spectroscopic techniques, including NMR and MS.
Keywords: synthesis